An ecocritical reading of flowers in Alice Walker’s The Color Purple - Arıkan, Arda (Journal of Human Sciences, 2015)
Flowers are one of the most popular motifs in verse as well as in prose. Many critics have noted that nature is at the core of Alice Walker’s epistolary novel The Color Purple (1983) in which depicting or writing about flowers requires special attention. However, in Alice Walker’s The Color Purple, flowers are depicted and written about to convey strong negative emotions as well as positive ones. In this study, how flowers are depicted or written about in the novel is studied through an ecocritical lens. I argue that Walker’s use of flowers provides examples of the vitality of a hopeful existence especially when various flowers mentioned in the novel are considered along with the seasonal changes organically affecting such floral richness. I equally argue that Walker uses flowers to show the change experienced by the major character, Celie. In that sense, Walker’s flowers are in direct coexistence with the major character, Celie.